Pemberdayaan Anak Pesisir dalam Pengembangan Talenta melalui Rumah Literasi Life Skill Berbasis Internet dan Social Community - Bayhaqky Bayhaqky; Marlya Fatira AK; Lailan Amelia Harahap; Ananda Aqilla Aqsa; Ulya Syafrina Saragih; Zuhratul Husna (Jurnal Ilmiah Madiya (Masyarakat Mandiri Berkarya), 2026)
Limited access to quality education, inadequate basic literacy skills, insufficient learning facilities, and the underutilization of information technology remain major challenges to fostering the talents of children living in coastal areas. These challenges are evident in Kwala Besar Village, Secanggang District, Langkat Regency, North Sumatra, where the population of 1,587 experiences low educational participation, limited access to non-formal learning facilities, and a lack of sustainable mentoring outside formal schooling. As a result, many children have inadequate literacy and numeracy skills, limited digital literacy, and few opportunities to develop their talents, creativity, and life skills. This community service program aimed to empower coastal children by supporting talent development through the establishment of the RULIFE Literacy House, a life-skills learning center based on internet technology and community engagement. The program adopted a participatory approach consisting of needs assessment, program planning, establishment of the literacy house, provision of internet-based learning facilities, literacy and life skills education, mentoring by the RUMNET social community, and continuous monitoring and evaluation. The program successfully served 128 children through literacy-enhancement and talent-development activities. It also provided a representative learning environment, internet-supported educational resources, an educational website, and strengthened collaboration among higher education institutions, the village government, and community volunteers in delivering sustainable nonformal education. The program improved children's literacy and numeracy competencies, digital literacy, life skills, self-confidence, and opportunities to explore their individual talents through interest-based learning activities. Overall program achievement reached 96%, as reflected by improved literacy outcomes, the establishment of a community-based literacy center, and the implementation of a sustainable mentoring system. This program helps strengthen community-based non-formal education while offering a collaborative and sustainable empowerment model to develop the talents of coastal children in the digital era.